Characterization of a GEM-based scintillation detector with He–CF4 gas mixture in clinical proton beams. (18th March 2016) - Nichiporov, D; Coutinho, L; Klyachko, A V
Abstract: Accurate, high-spatial resolution dosimetry in proton therapy is a time consuming task, and may be challenging in the case of small fields, due to the lack of adequate instrumentation. The purpose of this work is to develop a novel dose imaging detector with high spatial resolution and tissue equivalent response to dose in the Bragg peak, suitable for beam commissioning and quality assurance measurements. A scintillation gas electron multiplier (GEM) detector based on a double GEM amplification structure with optical readout was filled with a He/CF4 gas mixture and evaluated in pristine and modulated proton beams of several penetration ranges. The detector's performance was characterized in terms of linearity in dose rate, spatial resolution, short- and long-term stability and tissue-equivalence of response at different energies. Depth-dose profiles measured with the GEM detector in the 115–205 MeV energy range were compared with the profiles measured under similar conditions using the PinPoint 3D small-volume ion chamber. The GEM detector filled with a He-based mixture has a nearly tissue equivalent response in the proton beam and may become an attractive and efficient tool for high-resolution 2D and 3D dose imaging in proton dosimetry, and especially in small-field applications.